Impact of face masks on exercise capacity and lactate thresholds in healthy young adults - Rudi, W. S.; Maier, F.; Schüttler, D.; Kellnar, A.; Strüven, A. K.; Hamm, W.; Brunner, S. (International Journal of Sports Physiology and Performance, 2022)
Background: Although many countries have introduced strict guidelines regarding mouth and nose coverage in public to contain infection rates during the SARS-CoV-2 pandemic, more information is needed regarding the impact of wearing face masks on lactate thresholds (LT) and performance parameters during exercise.